2014
DOI: 10.1002/pros.22848
|View full text |Cite
|
Sign up to set email alerts
|

miR‐34a is an intracellular and exosomal predictive biomarker for response to docetaxel with clinical relevance to prostate cancer progression

Abstract: BACKGROUND. Docetaxel-resistance limits successful treatment of castration resistant prostate cancer. We previously demonstrated that extracellular vesicles (exosomes) may play a role in regulating docetaxel resistance. Here, we investigated intracellular and extracellular (exosomal) miRNAs related to docetaxel resistance. METHODS. Following global miRNA profiling of cell line models of docetaxel-resistance and their corresponding exosomes, we investigated the clinical relevance of four selected miRNAs (miR-59… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
141
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(157 citation statements)
references
References 61 publications
(85 reference statements)
3
141
0
2
Order By: Relevance
“…16 More importantly, exosomes-shuttling miRNAs probably conferred this resistance delivery. Followed by these studies, more and more evidence confirmed this observation in other cancers including breast cancer, prostate cancer, hepatocellular cancer, [17][18][19][20] and so on. However, similar to our previous study, most of these literatures mainly reported this phenomenon and few researchers 13 conduct in-depth study and systematically explore its detailed mechanism.…”
Section: Introductionmentioning
confidence: 65%
“…16 More importantly, exosomes-shuttling miRNAs probably conferred this resistance delivery. Followed by these studies, more and more evidence confirmed this observation in other cancers including breast cancer, prostate cancer, hepatocellular cancer, [17][18][19][20] and so on. However, similar to our previous study, most of these literatures mainly reported this phenomenon and few researchers 13 conduct in-depth study and systematically explore its detailed mechanism.…”
Section: Introductionmentioning
confidence: 65%
“…Unfortunately, there is not a consensus in miRNAs selected for these studies neither congruence with results published in blood. On the other hand, miRNAs were not associated with biochemical recurrence [123], PSA serum levels [126] or Gleason score [122,126], although according to Lewis et al [49], miR-888 measured in supernatant, but not in pellet, is associated with high-grade PCa. Finally, the value of miRNAs in the detection of PCa could increase in association with other tests.…”
Section: Mirnas In Urine In Prostate Cancermentioning
confidence: 99%
“…However, no studies are currently available about miRNAs in urinary exosomes in PCa, even when they have been widely explored in benign nephropathies [119,120]. Table 4 presents published results about miRNAs in urine, showing AUCs between 0.639 and 0.769 [49,86,88,98,[121][122][123][124][125][126][127][128]. Unfortunately, there is not a consensus in miRNAs selected for these studies neither congruence with results published in blood.…”
Section: Mirnas In Urine In Prostate Cancermentioning
confidence: 99%
“…Regarding other important factors, it has been observed that the miRNAs content of exosomes plays a role in docetaxel resistance. mir-34a that was significantly decreased in prostate cancer versus normal tissues as well as in urine, regulates BCL-2 and may in part, regulate the response to docetaxel [76,77].…”
Section: Exosomes and Prostasomesmentioning
confidence: 99%